Transient phenotypic changes in endothelial cells and pericytes in neonatal mouse retina following short‐term blockade of vascular endothelial growth factor receptors. Issue 5 (5th January 2018) - Morita, Akane; Mori, Asami; Arima, Shiho; Sakamoto, Kenji; Nagamitsu, Tohru; Ishii, Kunio; Nakahara, Tsutomu
ABSTRACT: Background : A short‐term interruption of vascular development causes structural abnormalities in retinal vasculature. However, the detailed changes in vascular components (endothelial cells, pericytes, and basement membranes) remain to be fully determined. The present study aimed to provide a detailed description of morphological changes in vascular components following a short‐term interruption of retinal vascular development in mice.Results : Two‐day treatment of neonatal mice with the vascular endothelial growth factor (VEGF) receptor tyrosine kinase inhibitor KRN633 (10 mg/kg, subcutaneously) on postnatal day (P)0 and P1 (P0/1) and P4 and P5 (P4/5) induced different degrees and patterns of impairment of retinal vascular development. Three days after completion of the treatment, the delayed radial vascular growth occurred in P0/1 group mice, whereas in P4/5 group mice, revascularization preferentially occurred in the central avascular area, and radial vascular growth remained suppressed by P10. Differences in α‐smooth muscle actin expression in pericytes were noted in the processes between normal vascular formation and vascular regrowth. The changes in vascular cells were associated with the hypoxia‐induced enhancement of VEGF expression in the superficial retinal layer.Conclusions : These findings suggest that the phenotype of vascular cells is altered following a short‐term interruption of vascular development in the retina. Developmental Dynamics 247:699–711, 2018 . © 2017 Wiley Periodicals, Inc. Key Findings: Treatment with the VEGF inhibitor interrupts retinal vascular development. After completion of the treatment, abnormal vascularization occurs. Phenotypic changes in endothelial cells and pericytes are induced by an interruption of vascular development.